The injecting 'event': harm reduction beyond the human. Issue 3 (27th May 2017) - Dennis, Fay
Abstract: Since the 1980s, the primary public health response to injecting drug use in the UK has been one of harm reduction. That is, reducing the harms associated with drug use without necessarily reducing consumption itself. Rooted in a post-Enlightenment idea of rationalism, interventions are premised on the rational individual who, given the right means, will choose to avoid harm. This lies in stark contrast to dominant addiction models that pervade popular images of the 'out of control' drug user, or worse, 'junkie'. Whilst harm reduction has undoubtedly had vast successes, including challenging the otherwise pathologising and often stigmatising model of addiction, I argue that it has not gone far enough in addressing aspects of drug use that go beyond 'rational' and 'human' control. Drawing on my doctoral research with people who inject drugs, conducted in London, UK, this paper highlights the role of the injecting 'event', which far from being directed or controlled by a pre-defined individual or 'body' was composed by a fragile assemblage of bodies, human and nonhuman. Furthermore, in line with the 'event's' heterogeneous and precarious make-up, multiple ways of 'becoming' through these events were possible. I look here at these 'becomings' as both stabilising and destabilising ways of being in the world, and argue that we need to pay closer attention to these events and what people are actually in the process of becoming in order to enact more accountable and 'response-able' harm reduction.